The effect of unsecured use of chemical pesticides on the environment and health in Iraq (Baghdad Science Journal, 2004)
The wide use of pesticides in recent years leads to rapid distribution of these pollutants in the environment (air, water and soil).They were transported by means of air or water to biological ecosystems. They become more toxic through the processes of biological magnification while some of them persist for along period.The aim of this work is to show the negative effect that chemical pesticides causes, and in the same to show their side effect on the environment and health in Iraq. We could conclude that the bad use of these chemicals could cause an urgent impact now or in the future. Governmental offices dealing with these materials should take the right measures to minimize the danger and the misuse of these chemicals by seeking alternatives ways of control. That may be safer and has no haphazard effect on health and environment, keeping in mind that mass media of clarification of the danger of these pesticides is fundamental duty to keep better health and environment in Iraq.